A series of novel carbohydrate-based carbon adsorbents were synthesized by self-propagating combustion for tetracycline removal. (July 2021) - Wang, Wei; Gao, Ming; Cao, Mengbo; Liu, Xun; Yang, Hongbing; Li, Yongsheng
Graphical abstract: Highlights: A series of novel adsorbents was prepared from glucose, maltose, and starch. The self-propagating combustion (SCS) is facile and time-saving (30 min). SCS has universality for the preparation of soluble carbohydrate carbon materials. The adsorbents prepared by SCS have excellent adsorption capacity (>375 mg/g). SCS can provide inspiration for the preparation of carbon-based materials. Abstract: Herein, a series of novel adsorbents derived from glucose, maltose, and starch zinc oxide (ZnO) loaded carbohydrate-based carbon materials (Zn-Cs) were synthesized by a fast and efficient self-propagating combustion synthesis method (SCS). The experimental results show that Zn-Cs exhibits excellent adsorption performance (>375 mg/g) to tetracycline, and the pseudo-second-order model and Freundlich model can better describe the adsorption data. The adsorption capacities of Zn-Cs were over 300 mg/g throughout the wide pH range (6–9), while various coexisting ions in the concentration range of 0–10 mg/L and the presence of humic acid had nearly no impact on the adsorption of tetracycline. Moreover, the adsorption experiment of simulated hospital wastewater shows that the adsorption capacity of Zn-Cs for tetracycline exceeds 185 mg/g. The adsorption mechanism of tetracycline are H-bond, complexation, and conjugation effect. This work provides an efficient, excellent versatility and time-saving strategy for preparing high-performance carbohydrate-based carbon materials for adsorbents.